PENGARUH INSTAGRAM SEBAGAI MEDIA PEMBERITAAN COVID 19 TERHADAP TINGKAT KEPERCAYAAN MAHASISWA: Studi Kasus Mahasiswa Universitas Muhammadiyah Surakarta - Nurmalinda, Yanuba; Purworini, Dian (Jurnal Common, 2022)
Abstract Along with the pandemic, there is now a lot of news emerging about Covid-19 circulating on Instagram social media. The news is not immediately able to make someone wonder about the occurrence of a pandemic crisis. This type of research is quantitative explanative. The population of this research is students of Muhammadiyah University of Surakarta who use social media Instagram with a sample of 97 respondents obtained from the slovin formula with purposive sampling technique. Data collection techniques in the study were carried out through a survey with a questionnaire instrument. The data analysis technique used is simple linear regression data analysis between the independent variable Instagram as the Covid-19 news media and the dependent variable is the level of student confidence. The results of this study explain that Instagram as a media for reporting on Covid-19 has a significant effect on the level of student trust. The influence of Instagram as media coverage of Covid-19 on the level of student confidence is 38.6% with a significance of 0.000. Keywords : Media, Covid-19 News, Instagram, Addiction Theory, Trust